1990
DOI: 10.1080/01418619008234943
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of (111) twist grain boundaries in f.c.c metals

Abstract: In this paper we have studied the atomic structures of (111)twist boundaries and investigated the applicability of the structural unit model which has previously been established for tilt boundaries and (001) twist boundaries by Sutton and Vitek. The calculations were carried out using two different descriptions of interatomic forces. A pair potential for aluminium, for which the calculations were made at constant volume, and a many-body potential for gold, for which the calculations were performed at constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Let us first focus on the twist GBs for the fcc symmetry. Figure 3 Burgers vectors b = a/2 110 , with a the lattice spacing, is the most favorite according to energy minimization [40,41]. This corresponds, e.g., to what has been observed in twisted, Au (111) thin films [42].…”
Section: Planar Grain Boundariessupporting
confidence: 60%
See 1 more Smart Citation
“…Let us first focus on the twist GBs for the fcc symmetry. Figure 3 Burgers vectors b = a/2 110 , with a the lattice spacing, is the most favorite according to energy minimization [40,41]. This corresponds, e.g., to what has been observed in twisted, Au (111) thin films [42].…”
Section: Planar Grain Boundariessupporting
confidence: 60%
“…It consists of a hexagonal network formed by three sets of dislocation directions ξ i [highlighted in Fig 3(a) by red dashed lines]. When considering low angle twist boundaries, such a network made of dislocations with Burgers vectors b = a/2 110 , with a the lattice spacing, is the most favorite according to energy minimization [40,41]. This corresponds, e.g., to what has been observed in twisted, Au (111) thin films [42].…”
Section: Planar Grain Boundariesmentioning
confidence: 99%
“…A more recent study [ 121 has focused on the computed energy/misorientation relationship for [ill] boundaries covering the entire misorientation range (0' 5 8 5 60") and found the energy curve to be symmetric with respect to 60°, as expected, and exhibit a deep cusp at that location. An additional study [13] has revealed minor cusps at angles intermediate in misorientation and has related the computed atomic structures to the structural unit model.…”
Section: Previous Studies Of [Lll] Twist Boundary Structuresmentioning
confidence: 98%
“…The simulation size is set as in the setup FCC 3, corresponding to a square domain of side length ∼ 80a fcc . They are also aligned along the [111] direction, therefore their growth is expected to form a (111) twisted GB with a typical hexagonal arrangement of defects [22,43,44]. Fig.…”
Section: Application: Growth Of Polycrystals With Dislocationsmentioning
confidence: 99%
“…The simulation size is set as in the setup fcc 3, corresponding to a square domain of side length ∼80a fcc . They are also aligned along the [111] direction, therefore their growth is expected to form a (111) twisted GB with a typical hexagonal arrangement of defects [22,43,44]. Figure 6 reports four stages during the evolution in terms of A>0 along with the dislocation networks at the resulting planar GB illustrated as insets.…”
mentioning
confidence: 99%